High pressure homogenization – An update on its usage and understanding - Inguva, Pavan; Grasselli, Silvia; Heng, Paul W.S. (Chemical engineering research & design, 2024)
Despite being a technology of several decades, high pressure homogenization (HPH) remains widely used in food and pharmaceutical industries, often as an essential unit operation in liquid product processing. Continual advances in the technology are made on multiple fronts, on equipment innovations by the manufacturers, new applications by users, and advances in process understanding by multidisciplinary scientists alongside subject matter experts amongst industry practitioners. While HPH is comparatively simple conceptually, the homogenization process involves complex engineering physics which is influenced by the varied processing conditions and highly diverse inputs with each use-case requiring its own treatment. The successful application of a HPH process indubitably requires practitioners to draw upon insights from multiple domains and the optimization for each case. Thus, this timely review aims to outline the more recent trends and advancements in HPH process understanding and novel applications involving HPH from both academic and industrial perspectives. •Review of modern applications of High Pressure Homogenization (HPH) in academia and industry.•Advances in food and beverage, pharmaceutical and biotechnology, and materials and chemicals sectors are covered.•Detailed review of modern theoretical, computational, and experimental methods to analyze and understand HPH processes.•Industrial perspectives and case studies from industrial application of HPH in various settings are presented.